2019
DOI: 10.1111/bph.14592
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin eugenol ester attenuates oxidative injury of vascular endothelial cells by regulating NOS and Nrf2 signalling pathways

Abstract: Background and Purpose: Aspirin eugenol ester (AEE) is a new drug compound synthesized by combining aspirin with eugenol. It was reported to possess antithrombotic, anti-atherosclerotic, and anti-oxidative effects. However, its molecular mechanism against oxidative injury is unclear. This study investigated how AEE affected the oxidative injury of vascular endothelial cells in vivo and in vitro. Experimental Approach: A hamster model of atherosclerosis induced by a high fat diet (HFD) and an in vitro model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…Similar to the previous results of m, AEE alone did not affect the level of intracellular ATP, while AEE pretreatment significantly inhibited the decrease of intracellular ATP concentration induced by PQ ( Figure 3C). These results suggested that AEE could significantly reduce PQ-induced mitochondrial dysfunction as a threshold effect at 1.0 µM by inhibiting intracellular oxidative stress, which are similar to previous study (Huang et al, 2019).…”
Section: Aee Alleviates Pq-induced Mitochondrial Dysfunction In Brl-3supporting
confidence: 91%
See 4 more Smart Citations
“…Similar to the previous results of m, AEE alone did not affect the level of intracellular ATP, while AEE pretreatment significantly inhibited the decrease of intracellular ATP concentration induced by PQ ( Figure 3C). These results suggested that AEE could significantly reduce PQ-induced mitochondrial dysfunction as a threshold effect at 1.0 µM by inhibiting intracellular oxidative stress, which are similar to previous study (Huang et al, 2019).…”
Section: Aee Alleviates Pq-induced Mitochondrial Dysfunction In Brl-3supporting
confidence: 91%
“…All experiments and data analysis were performed according the blinding principles (Altman et al, 1983;Huang et al, 2019). Statistical analyses were performed using SAS 9.2 (SAS Institute Inc., Cary, NC).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations